The role of thermodynamically stable configuration in enhancing crystallographic diffraction quality of flexible MOFs - He Zhao (Elsevier, 2021)
Summary: Single-crystal X-ray diffraction (SCXRD) is a widely used method for structural characterization. Generally, low temperature is of great significance for improving the crystallographic diffraction quality. Herein we observe that this practice is not always effective for flexible metal-organic frameworks (f-MOFs). An abnormal crystallography, that is, more diffraction spots at a high angle and better resolution of diffraction data as the temperature increases in the f-MOF (1-g), is observed. XRD results reveal that 1-g has a reversible anisotropic thermal expansion behavior with a record-high c-axial positive expansion coefficient of 1,401.8 × 10−6 K−1. Calculation results indicate that the framework of 1-g has a more stable thermodynamic configuration as the temperature increases. Such configuration has lower-frequency vibration and may play a key role in promoting higher Bragg diffraction quality at room temperature. This work is of great significance for how to obtain high-quality SCXRD diffraction data.